Stability assessment, Avayalik Island Cluster, Labrador, Canada, 800-1000 CE - Susan A Kaplan (Arctic Data Center, 2018)
This Rapid Response Research (RAPID) award funded two weeks of fieldwork in northern Labrador, Canada. Parks Canada provided Kaplan the vessel, its crew, and polar bear monitors free of charge to accomplish the project. The goal of the fieldwork was to assess the stability of a Middle Dorset (800 CE to 1,000 CE; CE meaning Common Era or the equivalent of 1,216 years ago to 1,016 years ago as of the present date: 2016 CE) archaeological site (Avayalik-1, House 1), located on an outer island 25 miles south of the tip of Labrador. Researchers investigated the vulnerability of Avayalik-1 to rising sea levels and the thawing of permafrost, with the intention of contributing to discussions on how to assess, monitor, and preserve such sites. This information is of great interest to the scientific community, culture resource managers, and also to the indigenous residents who are in many cases the decedents of the original occupants. Avayalik-1, House 1 is a scientifically unique Middle Dorset site. It was last investigated in 1978, and yielded organic artifacts and faunal remains unsurpassed in quantity and preservation by any other Labrador Middle Dorset sites due to the fact the cultural deposits were permanently frozen. However, given the current warming of the Arctic and the rapid thawing of permafrost, many Arctic heritage sites thought for decades to be safe while in the frozen ground are under threat. Avayalik-1 is such a site. The dataset contains specific archaeology site locations, photographs, fieldnotes, and an archaeology collection inventory. The information is being used to assess the stability of Avayalik-1, a Paleoeskimo site of importance to understanding the prehistory of Labrador, Canada. According to the terms of the research permit, the data collected must be deposited with Parks Canada, the archaeology office of the Province of Labrador-Newfoundland, and Nunatsiavut Archaeology Office. The data can be accessed through those repositories only, for Canada considers exact locations and the contents of archaeological sites protected information. Once the collections are across the border and analyzed they will be published and the data deposited with the approved repositories.